2011
DOI: 10.1159/000327531
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heliox in the Management of Neonates with Meconium Aspiration Syndrome

Abstract: Background: Helium-oxygen mixture (heliox) ventilation has been known as an alternative treatment in patients with airway obstruction. Because of the physical properties of heliox, mechanical ventilation with this gas mixture may offer advantages in the management of respiratory failure associated with meconium aspiration syndrome (MAS). Objectives: The purpose of this pilot study was to assess the effect of short-term mechanical ventilation with heliox in newborns with MAS on vital signs, oxygenation, acid-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Conventional ventilation with heliox (helium and oxygen mixture) was found to reduce work of breathing, improve oxygenation and CO 2 elimination, as well as enhance the distribution of gas within the respiratory system 2 . Findings from previous studies on heliox application in newborns during mechanical ventilation are encouraging 5 7 . However, knowledge about the physiological effects of this gas mixture during the non-invasive ventilation (NIV) in premature infants is limited.…”
Section: Introductionmentioning
confidence: 93%
“…Conventional ventilation with heliox (helium and oxygen mixture) was found to reduce work of breathing, improve oxygenation and CO 2 elimination, as well as enhance the distribution of gas within the respiratory system 2 . Findings from previous studies on heliox application in newborns during mechanical ventilation are encouraging 5 7 . However, knowledge about the physiological effects of this gas mixture during the non-invasive ventilation (NIV) in premature infants is limited.…”
Section: Introductionmentioning
confidence: 93%
“…In a pilot study in 8 newborns who were mechanically ventilated in a pressure-controlled SIMV mode because of respiratory failure due to meconium aspiration, 80% heliox was administered for 1 h [38]. There was a trend towards increased expiratory tidal volumes, minute ventilation and a peak expiratory flow rate during heliox ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, heliox administration in 10 infants who were studied before extubation was associated with a reduction in their work of breathing 50. A pilot study of eight ventilated neonates with meconium aspiration syndrome demonstrated that mechanical ventilation when heliox was administered was associated with a significantly lower fraction of inspired oxygen concentration and alveolar-arterial oxygen tension difference 51. Randomised trials are required to more robustly determine the efficacy of this therapy.…”
Section: Helioxmentioning
confidence: 99%